Perancangan Smart Library Assistant Menggunakan Voice Recognition Module - Jeremy Andika; Deosa Putra Caniago; M. Abrar Masril (LPPM-ITEBA, 2024)
This study proposes the design of a Smart Library Assistant using a Voice Recognition Module to facilitate book search in libraries. Despite the availability of digital books, many people still prefer physical books, and libraries remain a vital source of knowledge and information. However, finding books in a library can be challenging, especially when dealing with large collections. To address this issue, the study explores the use of voice recognition technology to create a smart library assistant that can help users locate books efficiently. The system will utilize the DFRobot Gravity offline voice recognition module to identify book genres and execute custom commands for finding books, eliminating the need for an internet connection. The research indicates that the voice recognition module, equipped with a microphone sensitive to -28db and capable of handling a maximum sound pressure level of 120db, enables the smart library system to accurately hear command words. The use of offline voice recognition modules, such as the DFRobot Gravity, can effectively simplify book searching in libraries. This technology allows the Smart Library Assistant to accurately identify genres and process voice commands without needing an internet connection. With a sensitive microphone capable of handling high sound pressure levels, the system provides an efficient solution for navigating large book collections.